تحديد تركيز الرصاص في بعض أغذية الأطفال المعروضة في أسواق مدينة اللاذقية - الحكيم, قصي (Latakia University Journal -Biological Sciences Series, 2018)
تصعب الإحاطة بكل أصناف الغذاء التي يستسيغها الأطفال عادة، ولكن أصنافاً معينة تستهوي الأطفال مهما اختلفت أنماط التغذية أو البلدان أو الثقافات التي ينتمون إليها مثل أنواع الشوكولاته والبسكويت والمقبلات النشوية المالحة، لذلك ركزت هذه الدراسة على تقدير مستويات الرصاص في بعض هذه الأغذية المتوافرة في أسواق المدينة والمتاحة لجمهور عريض من الأطفال بسبب سعرها المعتدل. تراوح تركيز الرصاص في عينات المنتجات الحلوة مثل الشوكولاتة والبسكويت الشوكلاتي والبسكويت المغطس بالشوكولاتة بين 0.036 و 0.209ppm، بينما كان أقل بوضوح في أصناف البسكويت الخالي من الكاكاو 0.021 -0.053 ppm وهذا المجال يقع ضمن الحدود المعروفة لأغذية الأطفال في البلدان المتقدمة، ولكنه يعكس مشكلة في موثوقية المادة الخام المستخدمة في هذه الصناعة، وهي الكاكاو. وكان تركيز الرصاص في عينات المقبلات المالحة مثل الشيبس وما يماثله من الأغذية النشوية بين 0.009 و 0.089ppm، بينما احتوت منتجات المواقع الحرفية التقليدية من معجنات نظيرة البيتزا (pizza) والحبوب والبذور المحمصة على مستويات من الرصاص بين 0.100 -0.342 ppm، وهي مستويات تقارب وتتجاوز في بعض العينات الحدود القصوى المسموح بها في أغذية الأطفال. It is hard to limit all kinds of food that children like, but there are certain desirable types by all children regardless of their food consumption patterns or countries or cultures. These foods include chocolate, biscuits, and salty taste food. This study focused on assessing levels of lead in some of these foodstuffs available in the markets of the city of Latakia, with moderate prices for children. Concentration of lead in samples of sweet products such as chocolate and biscuits dipped or mixed with chocolate ranged between (0.036 and 0.209ppm ) but it was less ( 0.021 and 0.053 ppm) in plain biscuits compared with the limits of known concentration of lead usually encountered in developed countries. This demonstrates the problem of the credibility of the raw material (cocoa) used in this industry. Lead concentration in salty appetizers such as chips and similar starchy foods ranged between (0.009 and 0.089 ppm), while classical popular products similar to pizza and toasted grains and seeds contained levels of lead ranging between (0.100 and 0.342ppm). These levels are similar but in some samples exceed the maximum levels permitted in children's food.